Achieving ultrahigh energy storage density in NaNbO3–Bi(Ni0.5Zr0.5)O3 solid solution by enhancing the breakdown electric field. Issue 18 (15th December 2020) - Chen, Hongyun; Chen, Xiuli; Shi, Junpeng; Sun, Congcong; Dong, Xiaoyan; Pang, Feihong; Zhou, Huanfu
Abstract: Developing high-energy storage materials is essential for the miniaturization and integration of electronic components. Traditional dielectric ceramics have drawbacks such as low energy storage and complex composition. One of the most effective methods to enhance the energy storage characteristics of dielectrics is to increase their breakdown field strength. In this study, lead-free (1- x )NaNbO3 - x Bi(Ni0.5 Zr0.5 )O3 [(1- x )NN- x BNZ] ceramics with high recoverable energy storage density ( W rec ) were fabricated by secondary solid-state sintering method. The BNZ was integrated into the NN as a secondary component to restrict the growth of grain and enhance the breakdown field strength. Ultimately, an excellent W rec of 4.90 J/cm 3 and an ultrahigh breakdown field strength ( E b ) of 500 kV/cm were obtained for the 0.88NN-0.12BNZ ceramic, which is related to the non-equivalent substitution of the B site. In addition, the sample remained notably stable at the test temperatures ranging from 20 °C to 120 °C and frequencies ranging from 10 Hz to 100 Hz. Excellent charge-discharge performances with high power density ( P D = 41.2 MW/cm 3 ) and a large current density ( C D = 588.9 A/cm 2 ), as well as an ultrafast discharge speed (60 ns) were obtained. All the aforementioned properties are potential conditions for high performance energy storage electronic ceramics.